Highly stable microtubular solid oxide fuel cells based on integrated electrolyte/anode hollow fibers - Meng, X.; Yan, W.; Yang, N.; Tan, X.; Liu, Shaomin (Elsevier, 2015)
The asymmetric YSZ hollow fibers have been prepared by a phase-inversion method, based on which, the integrated electrolyte/anode hollow fibers are fabricated via a vacuum-assisted impregnation of nickel nitrate. The content of NiO in the integrated hollow fibers enhances linearly from 0 to 42 wt.% with the impregnation cycles from 0 to 10. The porosity of the integrated electrolyte/anode hollow fibers decreases from 43% to 31% with the repeated impregnation and calcination of Ni catalyst. Its conductivity reaches up to 728 S cm−1 after 10 cycles of impregnation. And the mechanical strength of the integrated hollow fiber enhances from 128 to 156 MPa due to the increased NiO content. Based on the integrated electrolyte/anode hollow fibers, the prepared microtubular solid oxide fuel cells (MT-SOFCs) deliver a peak power density of 562 mW cm−2 after ten cycles of Ni impregnation. The cell stability has been verified in 40 thermal cycles with a steady OCV of 1.1 V and stable power density around 560 mW cm−2 operated at 800 °C.